THE QUALITY OF EARLY FOREIGN LANGUAGE LEARNING IN LITHUANIAN SCHOOLS - Bulajeva, Tatjana (Acta Paedagogica Vilnensia, 2007)
At present there is a growing tendancy in many EU countries to start a foreign language teaching at an early age. Early foreign language learning is not compulsory in Lithuanian schools, but on an experimental, voluntary basis it is already organised in many schools. Due to a rapidly changing role of foreign languages in a contemporary world, more attention is given to the quality of language teaching and learning. Language education policy orientations in Lithuania post-EU accession are directed at introduction of compulsory early foreign language teaching in the year of 2008. This article presents the research supported by the Ministry of Education and Science of Lithuanian Republic. The aim of this reseach is to analyze the quality of early foreign language learning in Lithuanian schools. The sample of 1105 primary (4th form)students from 21 different types of schools (primary, basic, secondary), representing different urbanization levels (city, regional and rural schools) was selected. Based on the National Core Curriculum and Early Foreign Language Education Standards there was an English language test developed. The results of testing of reading, writing and listening skills have shown that the mean test score is 31.3 out of 57 points possible. The analysis of test results has revealed the differences in test results by the level of urbanisation and type of school. There is no statistically significant difference in test results by gender and age. The distribution of test results according to the student achievement levels has shown that the low level was achieved by 4.2 per cent, the satisfactory level by 29.95 per cent, the main (basic) level by 55.48 per cent and the high level by10,05 per cent of tested 4th formers.